COMPARISON OF THE LEVELS OF STATIC AND DYNAMIC BALANCE IN OLDER ADULTS ENGAGED OR NOT ENGAGED IN A PHYSICAL ACTIVITY PROGRAM (Fiep Bulletin - online, 2011)
Aging is a process that affects all systems, including those that control body balance, and physical exercise may be one factor that contributes to the maintenance or improvement of balance levels in the elderly. This study aimed to compare the level of balance in elderly practitioners and non practitioners of programmed physical activities. The study included 30 subjects divided into two groups, 15 practitioners (PG) and 15 non-practitioners of physical exercises (NPG). To characterize the sample data, age, weight, height and BMI were collected. We used the stand up and walk test and to assess the dynamic balance and to assess the static balance, the one leg balance test was used. For comparison of test results between groups, we used the Students t test for independent samples. There was a significant difference in dynamic balance (6.0 0.5 2.4 vs 9.87, p = 0.00) and static balance with the right leg (21.0 11.9 vs 8, 4 9.2, p = 0.003) and with the left leg (20.0 vs 11.6 6.6 8.5, p = 0.0013). We conclude from this study that both the static and the dynamic balance were higher in physically active older adults.
Keywords: physical activities; balance; elderly